Is Virtual Reality Distraction Technique Effective to Cater Dental Pain and Anxiety Among Children? - Rabia Shafique, Aliya Ehsan, Sadia Afif, Daniyal Naeem Dar, Syed Mubashir Hussain Shah, Asma Shakoor, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The current study investigated the virtual reality distraction technique as an indicator of pain and anxiety reduction in children with an age between 6 to 9 years during short invasive dental procedure using salivary cortisol level as an indicator for measuring level of anxiety Method: This randomized clinical trial was conducted in a dental hospital of Lahore in the department of Pediatric dentistry. Data was collected from 30 patients which were divided in two groups. One group was containing patients who had screen time of less than 4hours whereas the other group contained patients who had screen time of more than 4hours in a day. Data was entered in SPSS version 25.0. Frequencies and percentages were calculated as descriptive analysis whereas comparison among both groups was made using Chi-Square test. Results: The results of chi-square test revealed that there is a significant difference in the pain perception of patients using virtual reality distraction technique during dental treatment (X2=4.701, P=.030). The results of paired sample t test revealed a significant difference between patients who has less than 4 hours screen time and patients who has more than 4 hours screen time in terms of salivary cortisol level (P=.001). Conclusion: The application of virtual reality distraction technique for the dental treatment of children is more effective among those who have more screen time as compared to the children who have less screen time